OPTIMIZING THE ROLE OF PARENTS IN SHAPING THE LOVE OF THE HOMELAND TO REALIZE THE PROFILE OF PANCASILA STUDENTS IN PARI CITY, PANTAI CERMIN DISTRICT, SERDANG BEDAGAI REGENCY - Widya, Rika; Rozana, Salma; Putri, Ranti Eka (Proceeding International Seminar of Islamic Studies, 2023)
The Independent Curriculum is one of the steps taken by the Ministry of Education and Culture in realizing the profile of Pancasila students. Various trainings and educational socialization have been carried out by the government. However, it seems to escape that in addition to formal education there is also education called informal education, namely children's education at home. Which parents are the teachers. To support government programs in realizing the profile of Pancasila students, parents should also take their role in shaping the love of the country for their children. Parents certainly need to be educated about what things will be done with their children. In line with this, researchers conducted research on optimizing the role of parents in shaping the love of the homeland to realize the profile of Pancasila students which is the goal of the current independent curriculum.